2015
DOI: 10.1007/s11071-015-2252-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of hydraulically driven parallel robot platform based on firefly algorithm

Abstract: A new cascade load force control design for a parallel robot platform is proposed. A parameter search for a proposed cascade controller is difficult because there is no methodology to set the parameters and the search space is broad. A parameter search based on firefly algorithm (FA) is suggested to effectively search the parameters of the cascade controller. We used unified mathematical model of hydraulic actuator of parallel robot platform. These equations are readily applicable to various types of proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Another such heuristic, the cuckoo search uses a heavy-tailed step length to explore the parameter space more efficiently [45]. The firefly algorithm models the patterns of light flashes used by fireflies to attract mates, and leads to very efficient exploration of this space as well [46]. These meta-heuristic methods can jointly estimate state information and optimize the parameters simultaneously, such as for controlling parallel robotic platforms [47].…”
Section: Related Workmentioning
confidence: 99%
“…Another such heuristic, the cuckoo search uses a heavy-tailed step length to explore the parameter space more efficiently [45]. The firefly algorithm models the patterns of light flashes used by fireflies to attract mates, and leads to very efficient exploration of this space as well [46]. These meta-heuristic methods can jointly estimate state information and optimize the parameters simultaneously, such as for controlling parallel robotic platforms [47].…”
Section: Related Workmentioning
confidence: 99%
“…The upper plate tracks the desired trajectory due to accurate control of actuator lengths and good coordination of all actuators. 2,6 Kinematics of Stewart platform…”
Section: Dynamic Relationship Within the Control Chambersmentioning
confidence: 99%
“…Thanks to the parallel linkage, more uniform distribution of loads and averaging of the positioning errors are accomplished. 2 Without it, the positioning errors would be accumulated.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results have indicated that CSA was superior to GA and PSO but less effective than BA in terms of capability of handling constraint conditions and optimal solutions. For the same problem with various types of proportional valves, and the combination of the cases of critical center, overlapped and underlapped valves, CSA has shown better efficiency than GA and PSO but also less performance than firefly algorithm (FA) [17]. In another study also about the optimal control of pneumatic-driven parallel robot platform [18], FA has also been successfully applied and resulted in promising improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In another study also about the optimal control of pneumatic-driven parallel robot platform [18], FA has also been successfully applied and resulted in promising improvement. The studies in [16], [17] have indicated that CSA has not been completely perfect for all optimization problems and there should be improvements in CSA. For a problem of chaotic systems parameter estimation, an improved CSA has been proposed by the combination of both the orthogonal design and simulated annealing operation [19].…”
Section: Introductionmentioning
confidence: 99%